Analysis of knowledge economy building in China and Belarus with global innovation rating - Xing, Wan; Kukareka, Diana V. (Journal of the Belarusian State University. Economics, 2018)
In the article, an attempt is made with the help of a global innovation index, assessing innovation potential and results, to reveal the reasons for such significant differences in the building of the knowledge economy in China and Belarus. Here we based on the report GII-2016 on the theme «Winning with Global Innovation», that is devoted to the role of globalization in the innovation process. The analysis of the growth of differences in the innovative development of China and Belarus was made, and the reasons for China’s progress and the growth of the backwardness of Belarus were outlined.
Keywords: global innovation index; knowledge economy; globalization; «advanced» modernization; scientific innovation process